TIM-3 Expression Level on AML Blasts Correlates With Presence of Core Binding Factor Translocations Rather Than Clinical Outcomes - Hong, Jian; Xia, Leiming; Huang, Zhenqi; Yuan, Xiaodong; Liang, Xinglin; Dai, Jifei; Wu, Zhonghui; Liang, Li; Ruan, Min; Long, Zhangbiao; Cheng, Xin; Chen, Xiaowen; et al. (Frontiers in Oncology, 2022)
Background T-cell immunoglobulin and mucin domain-containing molecule 3 (TIM-3) expresses on leukemic stem and progenitor populations of non-M3 acute myeloid leukemia (AML) as well as T lymphocytes. TIM-3 is thought to be involved in the self-renewal of leukemic stem cells and the immune escape of AML cells, however its correlation with AML prognosis is still controversial and worthy of further investigation. Methods we simultaneously assessed TIM-3 expression levels of leukemic blasts and T lymphocytes in the bone marrow of de novo AML patients using flow cytometry. The correlations of TIM-3 expression between leukemic blasts and T lymphocytes and the correlations of TIM-3 expression with various patient parameters were analyzed. In addition, the Cancer Genome Atlas (TCGA) data of AML patients were acquired and analyzed to verify the results. Results TIM-3 expression of CD34+ leukemic blasts (R2 = 0.95, p<0.0001) and CD34+CD38- leukemic stem cells (R2 = 0.75, p<0.0001) were significantly and positively correlated with that of the whole population of leukemic blasts. In addition, TIM-3 expression level of leukemic blasts correlated significantly and positively with that of CD8+ (R2 = 0.44, p<0.0001) and CD4+ (R2 = 0.16, p=0.0181) lymphocytes, and higher TIM-3 expression of leukemic blasts was significantly associated with a greater proportion of peripheral CD8+ T lymphocytes (R2 = 0.24, p=0.0092), indicating that TIM-3 on leukemic blasts might alter adaptive immunity of AML patients. Regarding clinical data, the presence of core binding factor (CBF) translocations was significantly correlated with higher TIM-3 expression of leukemic blasts (CBF versus non-CBF, median 22.78% versus 1.28%, p=0.0012), while TIM-3 expression levels of leukemic blasts were not significantly associated with the remission status after induction chemotherapy (p=0.9799), overall survival (p=0.4201) or event-free survival (p=0.9873). Similar to our results, TCGA data showed that patients with CBF translocations had significantly higher mRNA expression level of HAVCR2 (the gene encoding TIM-3) (median, 9.81 versus 8.69, p<0.0001), and as all patients in the cohort were divided into two groups based on the median HAVCR2 expression level, 5-year overall survivals were not significantly different (low versus high, 24.95% versus 24.54%, p=0.6660). Conclusion TIM-3 expression level on AML blasts correlates with presence of CBF translocations rather than clinical outcomes.